Reliability of an assessment used in formal accommodation services: Implications for adults with an intellectual disability - Milasinovic, Vesna; Buchanan, Angus (Informa Healthcare, 2013)
Background: The Revised Irrabeena Core Skills Assessment (RICSA) is used in formal accommodation services and evaluates the functional skills of adults with an intellectual disability. The assessment is used to inform training for skills development. This study focused on establishing evidence for interrater reliability of the RICSA. Method: The RICSA was completed by 101 staff members on 30 adults living in group homes. Interviews were conducted with 9 staff members in order to identify potential issues that may affect the reliability of the assessment. Interrater reliability was analysed using the intraclass correlation coefficient (ICC), and thematic analysis was conducted from the interview data. Results: The ICC values ranged from .63 to .73 across the 5 main domains of the RICSA. Conclusions: The agreement found may be regarded as unsatisfactory given that the use of the RICSA is to inform skills training for people with an intellectual disability.